DISCOURSE ANALYSIS OF NARRATIVE VOICE IN NOVELS - Shokirova Marhabo Sharifovna; Sobirova Umidaxon A’zamjon qizi (TADQIQOTLAR, 2025)
Abstract. This article examines the concept of narrative voice in novels from a discourse-analytical perspective. Narrative voice is understood as a linguistic and discursive construct that shapes how stories are told and interpreted. Drawing on theories of discourse analysis, narratology, and stylistics, the study explores how grammatical choices, deixis, modality, and speech representation contribute to the construction of narrative voice. Through qualitative textual analysis, the article demonstrates that narrative voice plays a crucial role in mediating meaning, ideology, and reader engagement in fictional discourse.